THE ANALYSIS OF STATE AND DEVELOPMENT OF AVIATION INDUSTRY OF RUSSIAN FEDERATION - M. Bogdanova (Publishing House of the State University of Management, 2017)
The article analyzes the state and development of the aviation industry of the Russian Federation, which is one of the most high-tech industries, maintains a high scientific, technical and industrial potential. The authors present the structure of the aviation industry and the composition of the Russian Air craft. The main ways to address the challenges facing the aviation industry of the Russian Federation, discussed state support for the industry. The article analyzes the investment in the development of the Russian aviation industry within the framework of the federal target programs.